L’éducation intégrale de la jeunesse française : la mainmise catholique sur un concept éducatif (1898-1939) - Fabien Groeninger (Éducation et Socialisation)
How did the Catholics take hold of a concept developed in the socialist and libertarian circles at the end of the 19th century? The Catholic sports and gymnastics federation, created in 1898, quickly became a mass youth organization. It reached its peak in the 1920s with leaders who were convinced that the integral education of young people was at the service of the nation. Thus, leaders feel the need to theorize in order to overcome reluctance, including on their own side. While Catholic integral education initially moved away from socialist conceptions through its religious dimension, militarism and rejection of diversity, discordant voices emerged in the 1930s and gradually brought the two antagonistic visions closer together.